If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-9x-12=-26
We move all terms to the left:
2x-9x-12-(-26)=0
We add all the numbers together, and all the variables
-7x+14=0
We move all terms containing x to the left, all other terms to the right
-7x=-14
x=-14/-7
x=+2
| 3.1=15.9-8w | | a/6=2/7 | | 3c+5=16+4= | | 24/4c=3 | | 2a=-1/2 | | p+1.5=(-9.84) | | x3.2+8.5=13.25 | | 90w-6=42 | | 24/x=8/6 | | 24/b=8/6 | | 2g=7.72 | | 2w^2+6w=28 | | (35-31)(x/2-11)+13=29 | | 4y–8=24 | | 6.49n+8.32=27.79 | | 952=p+792 | | 8f=9f−10 | | -39=r-770 | | 1/36=6^2x-4 | | 2x^2+10=13 | | -481=h-760 | | -8n+4=-28 | | (820-100)/(4x-2)-33=7 | | 52.47n-26.72=235.63 | | x/2+7/2=22 | | (29+7x)/5+(27-11)=26 | | 2(3x-5)=-12+6x | | k+770=466 | | `3x+5=50` | | 5(3m+1)=4(3m-4)-4m | | 8=6+v/5.12 | | 16x^2+3x+15=0 |